Efeito do pré-aquecimento realizado com Caps warmer e Dispenser nas propriedades mecânicas, contração pós-gel e tensão de contração de resinas compostas bulk fill - Ribeiro, Maria Tereza Hordones (2021)
To evaluate the effect of the preheating of different bulk fill composites at different temperatures and heating methods on the mechanical properties expressed by flexural strength, modulus of elasticity, degree of conversion, Knoop hardness, post-gel contraction and contraction stress. Three bulk fill composite resins of regular consistency available in capsules (FO - Filtek One Bulk Fill, 3M-ESPE; VC - VisCalor Bulk, VOCO; XF - x-tra Fil, VOCO) were preheated using VisCalor Dispenser (VOCO) a 65oC and Caps Warmer (VOCO) at 37oC, 54oC and 68oC. All materials were activated by light using a multipeak LCU (VALO Cordless, Ultradent) for 20 seconds. Post-gel contraction (Shr, %) was calculated using an extensometer. Flexural strength (FS, MPa), modulus of elasticity (E, MPa) were calculated by the 3-point flexion test. The degree of conversion (DC, %) using FTIR and Knoop hardness (KNH, N / mm2) were tested on the upper surfaces. The diametrical tensile strength (DTS) and the compressive strength (CS) were determined (n = 10). The contraction stresses were analyzed using three- dimensional finite element analysis. The data were analyzed by two-way ANOVA and Tukey's tests (α = 0.05). The different heating processes and temperatures did not influence the tested mechanical properties. The FS values were not influenced by the heating methods, temperature and type of composite resin tested. FO presented the lowest values of E, DC and KNH, VC presented intermediate values and XF presented the highest values. The DTS and CS values were not influenced by the heating methods, temperatures and type of composite resin tested. The heating process at 65oC performed with a dispenser and at 68oC and 54oC performed with warmer covers resulted in less shrinkage tension than preheating at 37oC using warmer covers, regardless of the bulk-fill resin compound. The VisCalor method has the lowest stresses. The new tested heating dispenser demonstrated efficiency in producing heating of composite resins, without influencing the mechanical properties. The heating of bulk viscous filler resin composites at higher temperatures (54 oC, 65oC and 68oC) reduced the shrinkage tension compared to heating at 37oC.